2022
DOI: 10.1002/hed.27238
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drug trifluoperazine as a potential therapeutic agent against nasopharyngeal carcinoma

Abstract: Background Trifluoperazine (TFP) is a typical antipsychotic primarily used to treat schizophrenia. In this study, we aimed to evaluate whether TFP can be used as a therapeutic agent against nasopharyngeal carcinoma (NPC) and identify its underlying molecular mechanisms. Methods We used NPC‐TW01, TW03, TW04, and BM to assess the anticancer effects of TFP by using cytotoxicity, wound healing, colony formation, and cell invasion assays. An in vivo animal study was conducted. RNA sequencing combined with Ingenuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Drug repurposing is the practice of utilizing clinically tested drugs in the market for alternative pathologies . Previous findings and published reviews have demonstrated the highly antiproliferative effects and therapeutic potential of antipsychotic phenothiazine (PTZ)-based drugs that act via different mechanisms including modulation of autophagy, membrane disruption/permeabilization, efflux pump inhibition, calcium overload, and/or other cell signaling pathways. For instance, thioridazine selectively targets leukemia cancer stem cells of metastatic nature while halting cell cycle at G 0 / G 1 phase and prevents the migration of tumor cells . Haloperidol, fluphenazine, and flupentixol induce dose-dependent cell death in neuroblastoma and glioma cell lines , while perphenazine (PPH) has been shown to modulate negatively the cell cycle of SH-SY5Y neuroblastoma cell line .…”
Section: Introductionmentioning
confidence: 99%
“…Drug repurposing is the practice of utilizing clinically tested drugs in the market for alternative pathologies . Previous findings and published reviews have demonstrated the highly antiproliferative effects and therapeutic potential of antipsychotic phenothiazine (PTZ)-based drugs that act via different mechanisms including modulation of autophagy, membrane disruption/permeabilization, efflux pump inhibition, calcium overload, and/or other cell signaling pathways. For instance, thioridazine selectively targets leukemia cancer stem cells of metastatic nature while halting cell cycle at G 0 / G 1 phase and prevents the migration of tumor cells . Haloperidol, fluphenazine, and flupentixol induce dose-dependent cell death in neuroblastoma and glioma cell lines , while perphenazine (PPH) has been shown to modulate negatively the cell cycle of SH-SY5Y neuroblastoma cell line .…”
Section: Introductionmentioning
confidence: 99%
“…14 In recent years, studies have found that TFP has inhibitory effects on breast cancer, glioblastoma, lung cancer, etc. [15][16][17][18][19] TFP has also shown synergistic anti-cancer potential in combination with other anti-tumour drugs, exhibiting the ability to circumvent the multidrug resistance of cancer cells. [20][21][22][23][24] Since TFP has the tendency to cross the blood-brain barrier, it often has notable adverse effects on the central nervous system, such as drowsiness, dizziness and extrapyramidal reactions in patients, 25 which greatly affect its potential as an anti-cancer drug.…”
Section: Introductionmentioning
confidence: 99%